The Status of Assessment Literacy and Classroom Practice of Secondary Level Teachers - Sarala Luitel (Interdisciplinary Research in Education, 2021)
Assessment is the tool that measures the quality of education. This study was focused on the status of teachers’ assessment literacy and practice in the classroom. A case study of a mixed research approach was conducted within the Kathmandu Valley selecting three schools.The questionnaire, Interview schedule, and observation checklist were the main tools. There were 27 teachers teaching fundamental subjects (Mathematics, English, Science, and Social Study) at grades IX and X were chosen for the survey and one mathematics teacher from each school was selected for interview. Two schools were selected for the observation. The constructivist theory was used to justify the finding. The result showed the high literacy status of the teachers with mean 2.63> 2 where 93.83% of teachers were known about the 18 different assessment techniques but only 66.26% of teachers apply those techniques in the classroom for assessment.